Pengaruh Penentu Kompleksitas Struktur Modal Perusahaan Sektor Pertambangan Bursa Efek Indonesia - Indriati, Teti; Ma’mun, Sitti Zakiah; Maksar, Muhammad Sofian (Universitas Batanghari, 2024)
This study aims to determine the determinants of capital structure complexity in the mining sector listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. In this study, the factors that determine the complexity of capital structure include indicators of asset structure, company size, profitability, inflation, and interest rates, while the complexity of capital structure includes indicators of the size of the number of capital sources and the level of concentration of capital sources. The number of samples was 52 mining companies collected using purposive sampling technique. This study uses quantitative data obtained from data listed on the Indonesian Stock Exchange (IDX) and the World Bank portal, and uses panel data regression analysis techniques. The findings show that only asset structure has a significant positive influence on the complexity of capital structure, which is measured by the number of capital sources and the concentration of capital sources. Meanwhile, the variables of firm size, profitability, interest rate and inflation have no significant influence on the complexity of capital structure in mining companies.